Optimalisasi Pelayanan Kesehatan Melalui Integrasi Data Rekam Medis Rumah Sakit dan Puskesmas - Suwanto Sanjaya; Lola Oktavia (UIN Sultan Syarif Kasim Riau, 2015)
Each patient was treated at the hospital will be recorded in medical records at the hospital orclinic. Medical records of a patient in a hospital or health center is certainly not complete because patientstreated in different health centers and hospitals.Medical record separately in each health center and thehospital complicates the search and analyze medical history. Surely this can reduce the level of healthcare to patients. In this research, created a system that can integrate medical records each health centerand the hospital. Medical record data were taken from the Ibnu Sina hospital, Eria Bunda hospital, StabitaClinic, Nurul Shadri Clinic and Assyafni Clinic . Every business processes in hospitals and clinics traced tocreate a web service that will be parsing the medical records of each application to hospitals and clinics.With the implementation of the web service, medical record will be integrated with each other, thussimplifying the processing, and search history data medical records of patients. A complete medical recordhelps doctor to analyze disease and treatment process. This helps hospitals to improve health services forpatientsKeywords: Data Integration, Hospital, Medical Records, Patient, Web Service